2014
DOI: 10.11604/pamj.2014.19.85.3428
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of congenital heart diseases in Rwandan children with genetic defects

Abstract: IntroductionCongenital heart diseases (CHD) are commonly associated with genetic defects. Our study aimed at determining the occurrence and pattern of CHD association with genetic defects among pediatric patients in Rwanda.MethodsA total of 125 patients with clinical features suggestive of genetic defects were recruited. Echocardiography and standard karyotype studies were performed in all patients.ResultsCHDs were detected in the majority of patients with genetic defects. The commonest isolated CHD was ventri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…While the most common types detected of cyanotic congenital heart defects were tetralogy of Fallot 38.9%, complete AV canal 22.1%, 18.2% compared to many unfrequented types as double inlet left ventricle and truncus arteriosis (1.3%). These results are in accordance with studies in Gorgan, northern Iran [17], South distract in Iran [20] Rwanda [4], and Xinjiang in China [21]. The study was done in India presented ASD was the commonest lesion followed by VSD similar to our study [18].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…While the most common types detected of cyanotic congenital heart defects were tetralogy of Fallot 38.9%, complete AV canal 22.1%, 18.2% compared to many unfrequented types as double inlet left ventricle and truncus arteriosis (1.3%). These results are in accordance with studies in Gorgan, northern Iran [17], South distract in Iran [20] Rwanda [4], and Xinjiang in China [21]. The study was done in India presented ASD was the commonest lesion followed by VSD similar to our study [18].…”
Section: Discussionsupporting
confidence: 92%
“…In infancy and childhood, the diseases are considered the second leading cause of death [1][2][3]. Congenital heart diseases are the most prevalent types of birth defects [4] with the incidence of 10 per 1000 live births [5]. However, different studies reported variable incidence rates from about 4/1000 to 50/1000 live births [6].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ventricular septal defect and patent ductus arteriosus were the commonest congenital heart defects in our series (Teteli et al. 2014). …”
Section: Genetic Services In Rwandamentioning
confidence: 99%